MH17 Witnesses Tell BBC They Saw Ukrainian Jet. BBC Deletes Video. (Global Research, 2014)
On July 23, two days after the Russian Ministry of Defense presented a radar track of a Ukrainian SU-25 fighter climbing to within three kilometers of MH17, the BBC’s Russian service aired a report by correspondent Olga Ivshina. The report originated when Ivshina and her cameraman went in search of the field outside the town of Torez, …
Section: English